A reconfigurable hyperbolic metamaterial perfect absorber. Issue 6 (19th February 2021) - Behera, Jitendra K.; Liu, Kuan; Lian, Meng; Cao, Tun
Abstract : A dynamically reconfigurable perfect absorber operating in the near-infrared region by incorporating chalcogenide glass into hyperbolic metamaterials. Abstract : Metamaterial (MM) perfect absorbers are realised over various spectra from visible to microwave. Recently, different approaches have been explored to integrate tunability into MM absorbers. Particularly, tuning has been illustrated through electrical-, thermal-, and photo-induced changes to the permittivity of the active medium within MM absorbers. However, the intricate design, expensive nanofabrication process, and the volatile nature of the active medium limit the widespread applications of MM absorbers. Metal–dielectric stack layered hyperbolic metamaterials (HMMs) have recently attracted much attention due to their extraordinary optical properties and rather simple design. Herein, we experimentally realised a reconfigurable HMM perfect absorber based on alternating gold (Au) and Ge2 Sb2 Te5 (GST225) layers for the near-infrared (N-IR) region. It shows that a red-shift of 500 nm of the absorptance peak can be obtained by changing the GST225 state from amorphous to crystalline. The nearly perfect absorptance is omnidirectional and polarisation-independent. Additionally, the absorptance peak can be reversibly switched in just five nanoseconds by re-amorphising the GST225, enabling a dynamically reconfigurable HMM absorber. Experimental data are validated numerically using the finite-difference time-domain method. The absorber fabricated using our strategy has advantages of being reconfigurable, uncomplicated, and lithography-free over conventional MM absorbers, which may open up a new path for applications in energy harvesting, photodetectors, biochemical sensing, and thermal camouflage techniques.